The Impact of Incorporating Multiple Best Practices on Live Outcomes for a Municipal Animal Shelter in Memphis, TN - Kreisler, Rachael E.; Pugh, Alexis A.; Pemberton, Katie; Pizano, Sara (Frontiers in Veterinary Science, 2022)
Modern animal shelters are encouraged to adopt "best practices" intended to promote life-saving for the animals that enter their systems. While these best practices have been defined and widely promoted within the profession, few studies have tracked how making the recommended changes affects live release rates (LRR) and other shelter metrics. In 2017, the municipal animal shelter in Memphis, TN (Memphis Animal Services) implemented five new strategies and analyzed their resultant life-saving data. The interventions included managed strategic shelter intake, pet owner safety net, community cat return to field, transition of field services from punitive to assistive, and streamlined adoption and transfer protocols. The median LRR for cats prior to 2017 was 35% (IQR 22,36). After the intervention, the LRR increased to a median of 92% (IQR 92,94). The correlation between intake and euthanasia for cats prior to the intervention was significant (P < 0.001) and very strong (r = 0.982), while after there was no relationship (-0.165) and it was not significant (P = 0.791). The median LRR for dogs prior to 2017 was 25% (IQR 19,48). After the intervention, the LRR increased to a median of 87% (IQR 86,88). The correlation between intake and euthanasia for dogs prior to the intervention was significant (P < 0.001) and very strong (r = 0.991), while after there was a moderate relationship (-0.643) that was not significant (P = 0.242). The median LRR for kittens prior to 2017 was 34% (IQR 23,38), which increased (P = 0.001) to 92% (IQR 91,92) after intervention. The percent of kittens entering the shelter with an outcome of euthanasia decreased (P < 0.001), from a median of 59% (IQR 54,73) to a median of 3% (IQR 1,3). The median return to owner (RTO) rate for dogs increased (P = 0.007) from 10% (IQR 9,11) to 13% (IQR 13,13). Implementation of these best practices accelerated MAS’ progress towards a live release rate of at least 90%, particularly for cats, dramatically decreased kitten euthanasia, increased the RTO rate for dogs and severed the historical correlation between euthanasia and intake.